SELFDESCRIBE OF KEY VECTORS OF SCIENTIFIC ACTIVITY IN THE NEWEST BOOK OF STEPAN HOROB - Lutsak, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The review of book of Stepan Horob is the «Literature art signs of life: Study and theatre sciences articles of literature, research and publicist». – Ivano-Frankivs’k: Nova Zorya, 2009. – 390 s.